THU0404 Self-reported severity of gout in a primary care setting and associated factors – results from a gout survey in primary care. (15th June 2017) - Landgren, AJ; Dehlin, M; Bergsten, U; Sigurdardottir, V; Drivelegka, P; Zverkova, T Sandström; Jacobsson, L
Abstract : Background: Patients with gout are usually seen in primary care. There are numerous reports regarding severity of gout in cohort studies and patients seen in more specialized care, less is known about the spectrum of severity of the disease in primary care. Objectives: To describe the pattern of self-reported disease severity of gout and predictors thereof in a primary care setting. Methods: All patients above 18 with an ICD10-diagnosis of gout at a health care visit in primary care (Jan 2015 through Aug 2016) were identified from primary care within the Western Sweden Health Care Region (WSHCR). 941 patients were identified and included in the study. They were sent a questionnaire with questions regarding comorbidities, demographics, gout characteristics and Health Assessment questionnaire (HAQ) reflecting disability. Self-reported disease severity was assessed by a three-level Likert scale (mild, moderate, severe). Possibly associated factors were analyzed by bivariate logistic regression (binary outcome: mild vs. moderate/severe) models and factors that were statistically significant were further analyzed by multivariate analysis. Results: The response rate was 54%. Response rates were significantly lower in women overall and in men under the age of 50. Covariates that were significantly associated with more severe self-reported severity of gout in the bivariate logistic regression models (Table 1 ) were: female sex, hyperlipidemia, higher number of previous attacks, attack during last month, HAQ. In the multivariate analysis objective measures of gout severity such as more than ten previous attacks and attack during last month were strongly associated with the patients grading of severity, in addition to presence of hyperlipidemia (Table 1 ). Conclusions: Over 40% of patients with gout in a primary care setting rated their disease as moderate or severe. The validity of the patients rating was supported by other covariates reflecting disease severity. The observations that women and those with hyperlipidemia reported a more severe disease needs to be further explored. Disclosure of Interest: None declared